Percutaneous transforaminal endoscopic surgery combined with mini-incision OLIF and anterolateral screws rod fixation vs. MIS-TLIF for surgical treatment of single-level lumbar spondylolisthesis - Tianyao Zhou; Tianyao Zhou; Wenshuai Fan; Yutong Gu; Yutong Gu; Wu Che; Liang Zhang; Yichao Wang (Frontiers in Surgery, 2023)
ObjectiveOblique lumbar interbody fusion (OLIF) has been used to treat lumbar spine spondylolisthesis. However, it usually needs posterior pedicle screws fixation for biomechanical stability and possible posterior direct decompression for relieving neurologic symptoms. We use percutaneous transforaminal endoscopic surgery (PTES) combined with mini-incision OLIF and anterolateral screws rod fixation for surgical treatment of lumbar spondylolisthesis. The purpose of study is to evaluate the feasibility, efficacy, and safety of this method compared with minimally invasive surgery-transforaminal lumbar interbody fusion (MIS-TLIF).MethodsFrom July 2016 to May 2018, 65 patients of lumbar spondylolisthesis (L2–4) with neurologic symptoms were treated using PTES combined with mini-incision OLIF and anterolateral screws rod fixation (31 cases, group A) or MIS-TLIF (34 cases, group B) in this study. Operative duration, blood loss, incision length, fluoroscopy frequency, and hospital stay are compared. Preoperative and postoperative visual analog scale (VAS) pain scores of back and legs, Oswestry disability index (ODI), intervertebral space height, lumbar lordotic angle, operative segmental lordotic angle, and complications are recorded. The fusion status is assessed according to Bridwell's fusion grades.ResultsThe VAS score of back and leg pain and ODI significantly dropped after surgery in both groups (p < 0.001). There was no statistical difference of back and leg VAS score and ODI between two groups except that back VAS scores in group A were significantly lower than that of group B immediately after surgery (p = 0.000). Group A had significantly more intervertebral space height and operative segmental lordotic angle than group B postoperatively (p = 0.022, p = 0.002). Twenty-three segments (74.2%) were grade I and 8 segments (25.8%) were grade II in group A; 20 segments (58.8%) were grade I and 14 segments (41.2%) were grade II in group B at a 2-year follow-up (p = 0.194). No difference was observed in the complication rate between the two groups (6.5% vs. 5.9%, p = 0.924).ConclusionThe long-term clinical efficacy and complication rates of both groups are comparable. PTES combined with mini-incision OLIF and anterolateral screws rod fixation is a good choice of minimally invasive surgery for lumbar spondylolisthesis, which hardly destroys the paraspinal muscles and bone structures.